Overtopping on Breakwaters of Complex Cross Sections - Fernando Veloso Gomes (2007)
Over the past few decades, several formulas have been developed for predicting overtopping phenomena on coastal structures. Since most of them were intended for "standard" cross sections, the study of overtopping in structures with complex cross sections is not easy to perform using these formulas, even if their section is adapted to the "standard" model. In this paper the main questions concerning the differences obtained are discussed and some suggestions are presented in order to improve the evaluation of overtopping. The approach presented by HR Wallingford (1999) will be used as well as that of the Clash project by way of comparison.